Twee: A Novel Text-To-Speech Engine - Das, D; Hassan, H; Gupta, S (International Journal of Computer Sciences and Engineering, 2025)
With the advancement of technology and the widespread use of smart devices, the world has witnessed that the networking and/or the connectivity horizon has broadened to an exalted level. One of the prominent researches being undertaken in this digital era is the development of Text-to-Speech (TTS) engines; which is capable enough of offering more interactivity with the prevalent smart devices. There are various TTS engines available in the market currently, but these engines lack the capability of showing the effects of human voice e.g., they fail to provide credible indications of the sentiment, mood or emotional state of mind of the speaker etc. Further speaking, presently there is no comprehensible or consummate TTS engine that could replicate human behaviour and/or mannerisms with utmost precision and accuracy. This paper proposes a novel Text-to-Speech engine named ‘Twee’ whose pronunciation works in sync with real world human intelligence. The proposed system is an application of the interdisciplinary field of research whereby domains such as Natural Language Processing, Artificial Intelligence and Digital Signal Processing are amalgamated to perform sentiment analysis on text through the processing of phonemes. This system works well both in mono channel mode and in stereo mode and is capable of generating varied effects on a voice depending on the type of communication.